Ecosystem modelling to assess the impact of rearing density, environment variability and mortality on oyster production - P Cugier; Y Thomas; C Bacher (Aquaculture Environment Interactions, 2022)
The natural productivity of ecosystems, farming practices and mortality events drive the rearing density and growth of oysters in shellfish farming areas. The variability of these drivers, which can be of natural or anthropic origin, is therefore an important source of variation in the growth performance and production of shellfish. Knowledge of these variabilities and their relative importance help producers to anticipate their effects and adapt aquaculture practices in order to limit negative impacts and guarantee a constant, or at least acceptable, level of production. In this paper, we implement a 3D model coupling hydrodynamics, primary production and individual growth to predict oyster growth and production in Bourgneuf Bay (French Atlantic coast). We set up numerous scenarios to compare and hierarchize the impacts of aquaculture practices, environmental variability and mortality events on shellfish production. Our results allowed us to propose a simplified management tool, in the form of response functions, to optimize shellfish farming practices interannually. This tool will help shellfish farmers quickly recover production levels in response to variations in mortality and/or environmental conditions.